2000
DOI: 10.1002/(sici)1097-0150(2000)5:1<18::aid-igs3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of intraoperative computerized tomography in a newly developed spinal navigation technique

Abstract: Objective: We report on the first successful incorporation of intraoperative computerized tomography in spinal navigation procedures.Materials and Methods: All operations were performed with the aid of a Tomoscan M mobile CT system (Philips Medical Systems, Eindhoven, The Netherlands). The system comprises a mobile gantry, a mobile patient examination table, and a mobile workstation. Three different navigation systems were used: the EasyGuide (Philips Medical Systems, Eindhoven, The Netherlands), the Surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…11 Previous reports have showed an enhanced accuracy of instrumentation using point-matching registration with fixed landmarks in combination with the preoperative CT scan. 15,17,18 Glossop et al reported a reduction in registration errors when using implanted metal fiducial markers on a human cadaveric lumbar spine, which were imaged using CT. 15 Winkler et al implanted fiducial markers percutaneously in a patient with spondylolisthesis before surgery, and they were identified using CT. 17 These fixed landmarks helped improve the accuracy of intraoperative registration. The technique of intraoperative CT with marker screws was first used by Haberland et al 18 The use of marker screws helped achieve high accuracy of pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Previous reports have showed an enhanced accuracy of instrumentation using point-matching registration with fixed landmarks in combination with the preoperative CT scan. 15,17,18 Glossop et al reported a reduction in registration errors when using implanted metal fiducial markers on a human cadaveric lumbar spine, which were imaged using CT. 15 Winkler et al implanted fiducial markers percutaneously in a patient with spondylolisthesis before surgery, and they were identified using CT. 17 These fixed landmarks helped improve the accuracy of intraoperative registration. The technique of intraoperative CT with marker screws was first used by Haberland et al 18 The use of marker screws helped achieve high accuracy of pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of intraoperative CT with marker screws was first used by Haberland et al 18 The use of marker screws helped achieve high accuracy of pedicle screw placement. 18 The current study demonstrated the usefulness of marker screws (IMFs) in association with intraoperative 3-D imaging technology. Cervical spine pedicle screws were selected to test the new method, based on the difficulty of their insertion as well as the hypermobility of the cervical spine segments that makes navigation more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another new technique using computer-assisted surgery (CAS) for acquiring access in surgical decompression in spinal disease including cervical and thoracic disorders was shown to be useful 12,13,16 because it enables real-time feedback to the surgeon about the anatomical location of the thoracic spine. This type of surgery can help the surgeon map anatomical distances and safe trajectories, thereby decreasing the risk of neural damage.…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of this system is that the surgeon can scan as many times as necessary to achieve adequate orientation during decompressive surgery or implantation. [10][11][12][13]16 Several different approaches have been reported in the literature to treat TDH that can be classified into three categories: posterior, posterolateral, and anterior approaches. The first two approaches allow indirect decompression of the spinal cord and therefore carry the inadvertent cord injury risks.…”
Section: Discussionmentioning
confidence: 99%
“…The connection of an intra-operative CT scanner to a navigation system combined high application accuracy with the possibility of intra-operative quality checks according to Haberland and Ebmeier [11]. Following vertebral preparation, marker screws were applied to the vertebrae, to serve as fiducial markers.…”
Section: In Vitro Studiesmentioning
confidence: 99%